Pengaruh Citra Merek Terhadap Keputusan Pembelian Smartphone Vivo pada Dandi Speed Store Kecamatan Tanasitolo Kabupaten Wajo - Andi Nurwana; Andi Sumangelipu; M. Rais (Precise Journal of Economic, 2024)
This study aims to determine the influence of brand image on Vivo smartphone purchasing decisions. The population in this study were customers or consumers who made purchases at the Dandi Speed ​​Store in the Tanasitulu area of ​​Wajo Regency. The number of samples in this study was 55 people based on the Slovenian language formula according to Sugiyono (2017). Sampling was carried out by asking written questions or statements to respondents who made purchases. There are 3 (three) data analysis methods used, including simple linear regression analysis, correlation coefficient (r), and coefficient of determination (r2). The results of the study show that (1) the results of simple linear regression show an equation on the regression line Y = 10.156 + 0.533; (2) the results of the correlation coefficient test (r) produce a value of 0.493; (3) The results of the determination coefficient test (r2) produce a value of 24.3, namely 24%. This shows that brand image (X) only has an influence of 24%, which means it has little influence on purchasing decisions (Y) and the rest is only influenced by several other factors. Based on the results of the t-test, the value of the calculated t is 4.124 and the value of the t-table is 1.674, so H0 is rejected and H1 is accepted so it can be concluded that brand image (X) has a significant effect on purchasing decisions (Y) because the value of the calculated t> t-table.